Preparation of near-infrared quantum dots-herceptin conjugates for cancer imaging - Lee, Dong Kwan; Lee, Yong-kyu (Macromolecular research, 2010)
High-quality, near-infrared CdTe/CdSe core/shell quantum dots (QDs) formed in organic solvents can be dissolved completely in water using amphiphilic polymers, such as octylamine-modified poly(acrylic acid). The native hydrophobic ligands of QDs may be retained and used to interact with an amphiphilic polymer. Neutralized, octylamine-modified poly(acrylic acid) complexes hydrophobically capped CdTe/CdSe QDs, making them watersoluble. Fluorescence spectrophotometry showed that the quantum dot-polymer composites have strong photo-luminescence and are very stable in aqueous solutions. The surfaces of the water-soluble QDs can be conjugated to biomolecules, such as antibodies that target the human breast cancer cell line SK-BR-3, which is over expresses the HER-2 receptor (epidermal growth factor receptor-2). QD-Bioconjugates were characterized by UV-Vis spectroscopy, fluorescence photospectroscopy and confocal microscopy. Finally, it was confirmed that QDs-antibody bioconjugates efficiently labeled the cell membranes (targeted to HER-2 receptors) by comparing the water soluble QDs and QDs-antibody bioconjugates.